2001
DOI: 10.1002/app.1985
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and conductivity changes in a thermoplastic polyurethane‐based copolymer consisting of different soft segments

Abstract: Three different segmented thermoplastic polyurethanes (TPUs) were synthesized with 4,4Ј-methylenebis(phenyl isocyanate) as a hard segment and poly(ethylene glycol) (PEG) or poly(propylene glycol) (PPG) or an equal mixture of PEG and PPG with molecular 2000 as soft segments. The soft-segment component of TPU was changed to monitor modifications in chemical and physical properties among the three TPUs. Differential scanning calorimetry (DSC) and thermogravimetric analysis were used to monitor changes in thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…This is in agreement with observations of other authors, which indicate that in gel electrolytes obtained by impregnation with PC the charge transport becomes highly decoupled from motions of the polymer matrix [13,15,44]. In some cases, a slight bending of the dependence was observed at around 10 • C (more evident in the electrolytes with 56 and 70 wt% of MIX).…”
Section: Tpu-based Electrolytessupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with observations of other authors, which indicate that in gel electrolytes obtained by impregnation with PC the charge transport becomes highly decoupled from motions of the polymer matrix [13,15,44]. In some cases, a slight bending of the dependence was observed at around 10 • C (more evident in the electrolytes with 56 and 70 wt% of MIX).…”
Section: Tpu-based Electrolytessupporting
confidence: 93%
“…However, in case of gel electrolytes obtained by the impregnation of TPU with propylene carbonate (PC), most authors reported Arrhenius-type dependence [13,15,44]. This effect is believed to be associated with the improvement of salt dissociation as well as weakening of interaction between charge carriers and polymer matrix in the presence of PC.…”
Section: Ionic Conductivitymentioning
confidence: 88%
“…Solid State Ionics j o u r n a l h o m e p a g e : w w w. e l s ev i e r. c o m / l o c a t e / s s i is believed to take place almost entirely in the amorphous phase of a polymer matrix [10,11]. However, some reports have concluded that both soft and hard segments play a significant role in ionic transport [12].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 96%
“…The first of these peaks was fitted between 3400 cm -1 -3650 cm -1 to determine the free N-H groups, a second peak is fitted between 3340 cm -1 -3400 cm -1 to account for the carbonyl overtone and a final peak is fitted between 3250 cm -1 -3340 cm -1 to determine the contribution from hydrogen bonded N-H groups. 26 Once analysis was complete, the ratio of hydrogen bonded N-H groups to free N-H groups can be obtained. Following chain-extension, the ratio decreased from 7:1 for TMP-only to What influence greater phase mixing has on the adhesion and clarity will be discussed within section 3.3.…”
Section: Mdi-based Formulationsmentioning
confidence: 99%
“…Further information on the microphase morphology is obtainable from deconvolution of the carbonyl region. 25,26 The position of the peak labelled ester within table 6, will contain bands from both free urethane and free PCD ester groups which occupy the range 1740 cm -1 -1730 cm -1 . Of these functionalities, the ester will be dominant and any changes to the environment of these groups will lead to a noticeable change to the peak shape.…”
Section: Ur = Urethane U = Ureamentioning
confidence: 99%